Antitumor HPV E7-specific CTL activity elicited by in vivo engineered exosomes produced through DNA inoculation - Di Bonito P (Dove Medical Press, 2017)
Paola Di Bonito,1 Chiara Chiozzini,2 Claudia Arenaccio,2 Simona Anticoli,2 Francesco Manfredi,2 Eleonora Olivetta,2 Flavia Ferrantelli,2 Emiliana Falcone,3 Anna Ruggieri,3 Maurizio Federico2 1Department of Infectious, Parasitic and Immunomediated Diseases, Istituto Superiore di Sanità, Rome, Italy; 2National AIDS Center, Istituto Superiore di Sanità, Rome, Italy; 3Department of Veterinary Public Health and Food Safety, Istituto Superiore di Sanità, Rome, Italy Abstract: We recently proved that exosomes engineered in vitro to deliver high amounts of HPV E7 upon fusion with the Nefmut exosome-anchoring protein elicit an efficient anti-E7 cytotoxic T lymphocyte immune response. However, in view of a potential clinic application of this finding, our exosome-based immunization strategy was faced with possible technical difficulties including industrial manufacturing, cost of production, and storage. To overcome these hurdles, we designed an as yet unproven exosome-based immunization strategy relying on delivery by intramuscular inoculation of a DNA vector expressing Nefmut fused with HPV E7. In this way, we predicted that the expression of the Nefmut/E7 vector in muscle cells would result in a continuous source of endogenous (ie, produced by the inoculated host) engineered exosomes able to induce an E7-specific immune response. To assess this hypothesis, we first demonstrated that the injection of a Nefmut/green fluorescent protein-expressing vector led to the release of fluorescent exosomes, as detected in plasma of inoculated mice. Then, we observed that mice inoculated intramuscularly with a vector expressing Nefmut/E7 developed a CD8+ T-cell immune response against both Nef and E7. Conversely, no CD8+ T-cell responses were detected upon injection of vectors expressing either the wild-type Nef isoform of E7 alone, most likely a consequence of their inefficient exosome incorporation. The production of immunogenic exosomes in the DNA-injected mice was formally demonstrated by the E7-specific CD8+ T-cell immune response we detected in mice inoculated with exosomes isolated from plasma of mice inoculated with the Nefmut/E7 vector. Finally, we provide evidence that the injection of Nefmut/E7 DNA led to the generation of effective antigen-specific cytotoxic T lymphocytes whose activity was likely part of the potent, therapeutic antitumor effect we observed in mice implanted with TC-1 tumor cells. In summary, we established a novel method to generate immunogenic exosomes in vivo by the intramuscular inoculation of DNA vectors expressing the exosome-anchoring protein Nefmut and its derivatives. Keywords: nanovesicles, cytotoxic T lymphocytes, HIV-1 Nef, DNA vectors